Alcohol-associated liver disease and behavioral and medical cofactors: unmet needs and opportunities - Monnig, Mollie A.; Treloar Padovano, Hayley; Monti, Peter M. (Frontiers in Public Health, 2024)
Chronic liver disease is a leading cause of death in the US and is often preventable. Rising burden, cost, and fatality due to liver disease are driven by intensified alcohol use in the US population and the contributions of comorbid conditions. This mini-review focuses on the topic of liver health in the context of chronic, behavioral cofactors of disease, using research-based examples from the Brown University Center for Addiction and Disease Risk Exacerbation (CADRE). Our aim is to illustrate the current challenges and opportunities in clinical research addressing liver health in the context of behavioral and medical comorbidity and to highlight next steps in this crucial area of public health research and clinical care.